A Bibliography on Drug Testing in the Workplace - Armitage, Elizabeth (1987)
The following bibliography on mandatory drug testing has been compiled to accompany the Symposium on Drug Testing in the Workplace presented by the Journal of Law and Health on November 21, 1986, at the Cleveland Marshall College of Law. It is hoped that this bibliography will benefit not only legal educators and law students, but also the practicing attorney, librarians, employers and employees in the private and public sector, and those whose research and interests require an understanding of the issues raised by this subject